Sport specialization and low bone mineral density in female high school distance runners - Rauh, M. J.; Tenforde, A. S.; Barrack, M. T.; Rosenthal, M. D.; Nichols, J. F. (Journal of Athletic Training, 2020)
Context: Sport specialization may contribute to sport injury and menstrual dysfunction in female high school distance runners. Despite the recent growth in sport specialization, including among high school-aged runners, the association of sport specialization with bone mineral density (BMD) remains poorly described. Objective: To evaluate whether sport specialization was associated with BMD in female high school distance runners. Design: Cross-sectional study. Setting: Six high schools. Patients or Other Participants: 'Sixty-four female runners (age = 15.6 ± 1.4 years) who competed in cross-country or track distance events and were not currently on birth control medication. Main Outcome Measure(s): Each runner completed a survey on menstrual history and sport participation. Height and weight were measured, and dual-energy x-ray absorptiometry was used to measure whole-body, spine, and hip BMD. Each runner was assigned a sport specialization status: low (participation in =1 nonrunning sport and distance-running sport(s) for =8 mo/y); moderate (participation in both distance-running sport(s) =9 mo/y and =1 nonrunning sport(s) or limited to distance-running sport(s) for =8 mo/y); or high (participation only in distance-running sport(s) for =9 mo/y). Multivariable logistic regression was performed to determine the adjusted odds ratio and 95% confidence interval for sport specialization to BMD values, adjusting for body mass index and gynecological age. Results: Overall, 21.9%, 37.5%, and 40.6% of participants were high, moderate, or low sport specializers, respectively. Low BMD (spine or whole-body BMD z score < -1.0 [standardized by age and sex normative values]) was present in 23 (35.9%) runners. Compared with low sport specializers, high sport specializers were 5 times more likely (adjusted odds ratio = 5.42, 95% confidence interval = 1.3, 23.3; P = .02) to have low BMD. Conclusions: A high level of sport specialization in high school female distance runners may be associated with a heightened risk for low BMD. Further investigation of this association is warranted due to the health concerns about low BMD in adolescent female runners.